2020
DOI: 10.1001/jama.2020.6647
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation—Progress, Barriers, and New Opportunities

Abstract: As the current report from the Surgeon General states, it is never too late to quit, and it is time to make death and disability related to smoking a thing of the past.VIEWPOINT Opinion 2470

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 2 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Tobacco use is one of the major public health concerns and it is the most preventable cause of morbidity and mortality worldwide. It is estimated that 16 million adults are currently living with a smoking-related disease in the United States [1]. Cigarette smoking is the main source of tobacco consumption and it is also the most dangerous one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco use is one of the major public health concerns and it is the most preventable cause of morbidity and mortality worldwide. It is estimated that 16 million adults are currently living with a smoking-related disease in the United States [1]. Cigarette smoking is the main source of tobacco consumption and it is also the most dangerous one.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is also related to a higher susceptibility to pulmonary bacterial and viral infections, inducing structural changes in the respiratory tract and a decrease in immune response. In fact previous studies have shown that smokers are twice more likely to contract influenza and have more severe symptoms than non-smokers [1]. Moreover, in the current era of a viral pandemic due to the Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) causing the 2019 coronavirus disease (COVID- 19), despite the limited data available, smoking has been assumed to be possibly associated with adverse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a non-randomized control group reduced the threat to external validity, which limits the value of randomized controlled trials. In this era of promoting a smoke-free environment, we advised smokers identified by the identification system to quit and assisted those willing to quit after assessment [ 15 ]. Preference-based allocation is the fundamental step in implementing shared decision-making [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recruited prediabetic smokers receiving medical care at two hospitals in northern and central Taiwan, where a systematic identification system was applied to classify the tobacco addiction status of every patient in the outpatient clinics [ 15 ]. This study invited identified current smokers to undergo screening tests between August 2013 and January 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Lower quit success and cessation treatment utilization is likely attributed to various factors including misinformation about the health benefits of quitting in older age and false beliefs that older adults are unwilling or unlikely to be successful quitting. In fact, there are substantial health benefits of quitting cigarettes across the lifespan (Adams, 2020) and evidence suggests older adults quit at comparable, or higher, rates in cessation treatment compared to those younger (Chen and Wu, 2015).…”
Section: Introductionmentioning
confidence: 99%